Improved synthesis of the antifungal isobutyl o-coumarate catalyzed by the Aspergillus terreus type B feruloyl esterase - Ana Daniela Vega-Rodríguez (Elsevier, 2021)
Background: Hydroxycinnamic acids and some of their derivatives are molecules with interesting biological activities; for instance, hydroxylated hydroxycinnamic esters have proved to have antifungal properties, and thus the generation of these molecules is of industrial importance. In this study, the direct esterification capacity of the pure recombinant type B feruloyl esterase from Aspergillus terreus (AtFAE B) was evaluated by its ability to catalyze the synthesis of isobutyl o-coumarate, an interesting antifungal molecule. A ternary solvent system (isooctane/isobutanol/water) was employed to improve the synthesis of isobutyl o-coumarate, assessing different substrate concentrations, enzyme load, water percentages and pH and temperature values. Results: AtFAE B showed the highest initial rate at 18% (v/v) isobutanol and 50 mM o-coumaric acid, 0.04 mg/ml of enzyme, 4% (v/v) water without buffer and 40°C. AtFAE B half-lives at 30°C, 40°C and 50°C were 16.5 h, 1.75 h and 3.5 min, respectively. Thus, we decided to evaluate the bioconversion yield at 30°C, where the enzyme showed the highest operational stability. At this temperature, we obtained a yield of ~80% after only 8 h of reaction, using a 78:18:4 isooctane:isobutanol:water ternary solvent system, with 50 mM of o-coumaric acid. Conclusions: Under these improved conditions, the productivity was 1.06 g isobutyl o-coumarate/L*h with a biocatalyst yield of 209.6 kg isobutyl o-coumarate/kg free AtFAE B, demonstrating the promising potential of AtFAE B to accept the non-canonical o-coumaric acid as the substrate and to achieve the synthesis of isobutyl o-coumarate.How to cite: Vega-Rodríguez AD, Armendáriz-Ruiz MA, Grajales-Hernández DA, et al. Improved synthesis of the antifungal isobutyl o-coumarate catalyzed by the Aspergillus terreus type B feruloyl esterase. Electron J Biotechnol 2021;54. https://doi.org/10.1016/j.ejbt.2021.08.001